METODE TRIPLE EXPONENTIAL SMOOTHING HOLT-WINTERS UNTUK PERAMALAN JUMLAH WISATAWAN NUSANTARA DI KABUPATEN BANYUWANGI - Feby Indriana Yusuf; Dwi Hilda Anjasari (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
Forecasting is how to predict future event by considering the past data. This research aims to determine the results of the comparison of forecasting the number of domestic tourists in Banyuwangi by triple exponential smoothing method of Holt-Winters multiplicative and additive models in order to obtain the best model. The data used in this research is the number of domestic tourists in Banyuwangi period January 2010 to March 2018. The results showed that forecasting by the triple exponential smoothing method of multiplicative models with a smoothing constant α = 0.18; γ = 0.03 and β = 0.1 obtained the smallest value of MAPE and MSE.